Numerical simulation for in-plane behaviour of perforated framed masonry panels. (May 2014) - Liu, H. B.; Kong, J. C.; Wang, X. M.; Zhai, C. H.; Zhang, S. S.; Mei, H. Y.
Abstract : It has been long known that reinforced concrete (RC) frames enhanced masonry panels' performance, and masonry infill panels influenced strength and stiffness of the RC frames. Window openings are indispensable ingredients of masonry panels for functional reasons. However, few researches have been conducted on framed masonry panels with openings, although there are many numerical studies available on solid framed masonry panels' behaviour. In this study, a three-dimensional numerical model, which is based on the surface based contact cohesive interaction model and friction principle, is proposed for non-linear static analysis of perforated framed masonry panels. The numerical modelling is compared to the experiment studies found in the literature, which indicate that it can successfully predict not only the lateral capacity and stiffness but also the failure mode of the physical specimens. A parametric study is carried out to investigate the influence of the sizes of openings on in-plane behaviour of RC framed masonry panels.